PENGEMBANGAN MATERI AJAR BAHASA ARAB BERBASIS BIOLOGI UNTUK PERGURUAN TINGGI - Yelfi Dewi S; Muhammad Husni Shidqi; Adam Mudinillah (Lughawiyah: Journal of Arabic Education and Linguistics, 2021)
This study aims to produce valid, practical, and effective biology-based Arabic teaching materials for college students. The teaching materials are designed to support the Arabic language learning, especially for Biology Department, based on students’ needs and to increase their motivation in learning Arabic. This study used a development research approach with the Instructional Development Institute (IDI) model which consisted of three stages, namely front-end analysis, prototype, and assessment stage. The product was Arabic teaching materials with several characteristics. First, adjusting the content of teaching materials with topics in the field of biology. Second, the teaching materials are presented in a text, images that are relevant to the text, vocabulary, comprehending questions, relevant Qur'anic arguments, and sentence structures in a chart. Third, the language and content are adapted to the heterogeneous abilities of students. Based on  data analysis, it was found that the biology-based Arabic teaching materials were valid,  could increase students’ interest in learning Arabic, and made learning process become more effective. Therefore, this teaching materials could be used as an alternative  instructional material for Arabic learning in colleges.